SISTEM PERBAIKAN TRANSPORTASI (MATERIAL HANDLING) PADA INDUSTRI YANG MENGACU PADA PERUMUSAN ULANG BAN BERJALAN (BELT KONVEYOR) DAN SARANA TRANSPORTASI LAIN - Haryadi, Gunawan Dwi (ROTASI, 2001)
It still finds such the belt konveyor, truck, just the Material Handling, to move the material, components, andgood from a place to another place. The thing just it can implement the system, is not changeable from that system.That’s correct, because need the coordination such a function to move it. But it can learn by simpleable, jointable, anderaseable is three steps (basic) to forward the improvement.